Inheritance of Leaf Shape and Main Vein Color in Caladium - Zhanao Deng; Brent K. Harbaugh (EDIS)
The ornamental value of caladiums (Caladium x hortulanum Birdsey) depends, to a great extent, on leaf characteristics including shape, color, color pattern, and venation pattern. Broadly, caladium leaves are classified into three shapes: fancy, lance, and strap (Fig. 1).  This document is ENH1006, one of a series of the Environmental Horticulture Department, UF/IFAS Extension. Original publication date August 2005.